Physical activity and the transition from school to university: a cross-sectional survey among university students in Germany - Diehl, Katharina; Hilger-Kolb, Jennifer (Science & sports, 2016)
Introduction - The transition from school to university may be accompanied by different changes in lifestyle. We aimed to investigate whether students’ physical activity (PA) differs between school and university and which role change of residence plays. - Summary of facts and results - We analyzed data on 689 university students (69.5% female; mean: 22.7 years). The majority changed PA compared to school (less: 45.4%, more: 36.5%). Among those who were at the beginning of their studies and those who changed residence for the start of studies, the proportion of individuals having reduced PA was higher compared to their reference groups of students in higher semesters and students having not changed residence, respectively. Students visiting their hometown more frequently and staying there during semester break were more likely to have reduced PA. - Conclusion - Students who changed residence for starting studies seem to be a vulnerable group future intervention campaigns should focus on. Supporting those students to stay physically active during studies may be important to help them starting an active and healthy work life after graduation. Additionally, freshmen at universities may need more support to have the opportunity to stay physically active. - Résumé - Introduction - La transition de l’école à l’université peut être accompagnée par des changements de mode de vie. Nous avons cherché à déterminer si l’activité physique des étudiants diffère entre l’école secondaire et l’université et quel est le rôle joué par ce changement de lieu de vie. - Synthèse des faits et résultats - Nous avons analysé les données de 689 étudiants (69,5 % de femmes ; âge moyen : 22,7ans). La majorité des étudiants a changé son niveau d’activité physique en comparaison avec l’école secondaire (moins : 45,4 %, plus : 36,5 %). Parmi ceux qui débutaient leurs études et ceux qui ont changé de lieu de résidence pour aller à l’université, la proportion de ceux qui ont réduit leur activité physique était plus élevée que chez les étudiants plus anciens à l’université et chez les étudiants n’ayant pas changé de lieu de résidence. Les étudiants qui rentrent chez eux plus fréquemment et qui y séjournent pendant les vacances étaient plus susceptibles d’avoir réduit leur niveau d’activité physique. - Conclusion - Les étudiants qui ont changé leur lieu de résidence pour leurs études supérieures semblent être plus vulnérables et devraient être la cible de futures campagnes d’intervention. Aider ces étudiants à rester physiquement actifs pendant leurs études peut être important pour les amener à adopter un style de vie sain et actif dans la vie professionnelle. En outre, les étudiants de première année à l’université peuvent avoir besoin de plus de soutien pour rester physiquement actifs.
Gesehen am 10.12.2019
Available online 21 July 2016